Sistem Pendukung Keputusan Seleksi Wasit/Juri Olahraga Beladiri Pencak Silat Menggunakan Metode Profile Matching - Eka Syahputra (Forum Kerjasama Pendidikan Tinggi, 2021)
The process of selecting a qualified referee / jury is not an easy matter, it requires selection in the selection of referees / judges who are able to give satisfaction to all elements of the competition and there is no one-sided element. Selection is the stage to decide whether a participant is appropriate or not to be a referee / jury on IPSI. The decision taken is expected to be more objective so that the quality obtained is in line with expectations so that no party is harmed. The problem encountered in the previous selection was the absence of a clear assessment mechanism in the process of appraising prospective Referees / Judges. The previous selection of referees / judges only determines the aspects assessed in the selection, but does not have a clear assessment mechanism. This causes subjective decisions and results. Because the problem is often the selection results are not as expected. In addition, the previous selection has manual data processing. This if applied in the future will greatly reduce efficiency if the number of prospective Referees / Judges becomes numerous. To overcome the above problems, in this study proposed a Decision Support System using the Profile Matching Method that can choose Referees / Judges in accordance with the predetermined assessment, so that decision making can be done objectively. In addition, the system is also able to process registrant data quickly so that it can improve the efficiency of the selection process. The author chooses to use DSS Profile Matching method or commonly known as GAP Competence Analysis because this method is very suitable for use in human resource management where first determined the competencies (abilities) needed by a position. Competence of these abilities must be fulfilled by candidates who will be assessed for performance.